Monitoring the performance of Alpine skiers with inertial motion units: Practical and methodological considerations - Supej, M.; Holmberg, H. C. (Journal of Science in Sport and Exercise, 2021)
Although reliable feedback is crucial to improving the performance of competitive alpine skiers, the coach's eye may not be sensitive enough to detect small, but highly significant "mistakes". Monitoring of the performance of alpine ski racers by inertial motion units (IMU) has proven to be of value in this context and here we summarize practical and methodological aspects of this approach. Methodologically, the IMUs employed should combine high sampling frequencies with minimal signal drift. The sensors should be positioned to sense the movement of the bones in a given body segment while being protected as much as possible against impact with the ski gates. The data obtained, often synchronized with input from Global Satellite Navigation Systems (GNSS), are usually refined utilizing advanced biomechanical models and other computerized approaches. In practice, the combination of inertial sensors and GNSS allows accurate monitoring of skiing kinematics (technique) and the movement of the skier`s center-of-mass, also allowing analysis of both whole-body vibrations (WBV) and loss of mechanical energy. Presentation of the findings to coaches and athletes can be facilitated by synchronizing them with video recordings. Recent advances in IMU technology, including miniaturization, wireless communication, direct storage of data in the cloud, and processing with artificial intelligence may allow these sensors, in-combination with GNSS, to become real-time virtual alpine ski coaches, perhaps the next step in the development of this sport.